The Mediating Role of Affective Commitment between Creative Self-Efficacy, Authentic Leadership and Innovative Behaviour among Academic Employees of Higher Education Sector of Punjab, Pakistan - Dr Tasawar Javed; Shanayyara Mahmood; Saadia Khan; Habib Ullah (iRASD Journal of Management)
The higher education sector in developing counties has undergone through dynamic changes in recent era due to highly innovative and competitive environment. The phenomenon of innovation behaviour has gained intensive importance due to its long-lasting impact on performance of industry. The growth of knowledge-based economy is linked with innovative initiatives of employees of higher education sector. The proposed research contributes to the body of knowledge by explaining the relationship between exogenous constructs and innovative behaviour based on the theories of social exchange and social cognition as both theories explains the innovative behaviour of employees. The proposed research intends to bridge the research gap and inconclusive results between constructs to explain the innovative behaviour of academic employees of higher education sector. Moreover, the mediation role of affective commitment is incorporated for deeper insight of innovative behaviour. The data was obtained from academic employees of the public sector universities of Punjab, Pakistan through simple random sampling and was analysed on Smart-PLS. The authentic leadership considered as one of the crucially important factors at workplace that influence the affective commitment and innovative behaviour. The study reported significant results for hypothesis H1 that affective commitment influences the innovative behaviour, the hypothesis H2 reported that creative self-efficacy influences the innovative behaviour, they hypothesis H3 reports that authentic leadership influence the innovative behaviour. The hypothesis H4 depicts that creative self-efficacy influences the affective commitment, the hypothesis H5 found that authentic leadership influences the affective commitment. Similarly, the mediation role of affective commitment reported as significant between authentic leadership and innovative behaviour, however no mediation role of affective commitment was reported between creative self-efficacy and innovative behaviour. The findings of the study assist universities management to ensure the appropriate and supportive workplace initiatives for inclined innovative behaviours among employees. The future study may be conducted on comparison of highly innovative universities and less innovative educational institutes.